Structural Stability Electronic Structure and Bonding Properties of Tin Based Transition Metal Anodes LiM2Sn (M= Cd, Zn, Pd). (2016) - Gnanapoongothai, T.; Rameshe, B.; K.Shanmugapriya,; Murugan, R.; Palanivel, B.
Abstract: First principle calculations based on density functional theory have been performed to investigate the structural stability, electronic structure and Li + intercalation potential for the compounds LiM2 Sn (M= Cd, Zn, Pd). These electrode materials exhibit small percentage of volume change which accounts for excellent structural stability. The computed band structure along high symmetry lines in the Brillion zone, total and partial density of states clearly reveals that insertion of lithium to these electrode materials does not affect their metallic nature. The valence charge density calculation reveals the dominant ionic character of these compounds enables Li + accommodation.